Accounting-Driven Bank Monitoring and Firms’ Debt Structure: Evidence from IFRS 9 Adoption - Li, Xiao; Ng, Jeffrey; Saffar, Walid (Management Science, 2024)
International Financial Reporting Standard (IFRS) 9 is of practical relevance to banks because it requires intense monitoring of borrowers to record timely loan losses. Using data from 50 countries, we find that accounting-driven bank monitoring due to IFRS 9 adoption reduces firms’ reliance on bank debt relative to public debt. This finding is consistent with firms experiencing more costly bank monitoring after a shift in regulatory reporting that requires banks to monitor borrowers more intensely. In further analyses, we find that the negative effect of IFRS 9 adoption on bank debt reliance is more pronounced with more stringent regulatory supervision of banks, consistent with regulatory stringency exacerbating costly bank monitoring for firms. We also find that the negative effect is stronger when firms can more easily switch from bank debt to public debt financing, consistent with the relevance of switching costs in firms’ decisions to avoid costly bank monitoring. This paper was accepted by Suraj Srinivasan, accounting. Funding: This work was supported by the National Natural Science Foundation of China [Grant 71802205], the Program for Innovation Research, and the Program for Young Talents Cultivation [Grant QYP202103] in Central University of Finance and Economics. Supplemental Material: Data and the online appendix are available at https://doi.org/10.1287/mnsc.2022.4628 .